Transparent graphene-based counter-electrodes for iodide/triiodide mediated dye-sensitized solar cells - Rui Cruz (2014)
A new highly transparent and low cost counter-electrode for dye-sensitized solar cells was fabricated, comprised of a structured graphene film over nickel nanoparticles. Annealed nickel particles induced an enhanced restoration of graphene double bonds, which led to cells with energy conversion efficiencies similar to those using a conventional platinum electrode.